Estimating network effects and compatibility in mobile telecommunications - Michal Grajek (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2003)
This paper provides empirical evidence on the extent of network effects and compatibility between networks in mobile telecommunications. We specify a structural model of demand for mobile telephone service, which allows us to identify the parameters of interest from the S-shape of mobile service diffusion. The network effects are measured by the dependence of consumer willingness to pay on the installed base of subscribers. Compatibility is measured by the relative extent of cross- and own-network effects. As such, it indicates whether the network effects operate at the firm level, at the industry level, or at both. We then estimate this model for the Polish mobile telephone industry using quarterly panel data for the period 1996-2001. We find strong network effects, which give rise to upward-sloping demand, and, despite full interconnection of the mobile telephone networks, low compatibility. We show also that ignoring network effects in empirical models of emerging network industries might substantially bias downward the estimated price elasticity of demand. – – Der vorliegende Beitrag bietet empirische Evidenz für den Umfang von Netzwerkeffekten und Netzwerkkompatibilität in der Mobilfunktelekom-munikation. Wir spezifizieren ein strukturelles Modell für die Nachfrage von Mobilfunkdienstleistungen, das die Parameter von Interesse mithilfe der S-förmigen Funktion der Dienstleistungsdiffusion identifiziert. Die Netzwerkeffekte werden durch die Abhängigkeit der Zahlungsbereitschaft der Konsumenten von der installierten Abonnentenbasis gemessen. Netzwerkkompatibilität wird durch den relativen Umfang der Quer- und Eigen-Netzwerkeffekte gemessen. Sie weist darauf hin, ob Netzwerkeffekten auf Unternehmensebene, auf Industrieebene, oder auf beiden Ebenen bestehen. Dann schätzen wir das Modell für die Polnische Mobilfunkindustrie mit vierteljährlichen Paneldaten für 1996-2001. Wir stellen starke Netzwerkeffekte fest, die eine positive Steigung in der Nachfragefunktion verursachen, und – trotz der technisch vollständigen Querverbindung der Mobilfunknetze – niedrige Kompatibilität. Wir zeigen auch, dass das Übersehen von Netzwerkeffekten in empirischen Modellen von neuen Netzwerkindustrien die geschätzte Preiselastizität der Nachfrage signifikant nach unten verzerren kann.
Keywords: C51; D12; L96; 330; Structural Econometric Model; Network Effects; Compatibility; Mobile Telecommunications